PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN SOSIAL DI BURSA EFEK INDONESIA - UNIBA, Endang Masitoh Wahyuningsih (MAJALAH ILMIAH GEMA, 2012)
This study is aimed to know the influence of company characteristics in which contains of size of company, profitability, leverage and company operational coverage on social statement level with other characteristics such like industrial type, independent commissionaire board composition and also commissionaire president educational level as the control variable. This study uses secondary data from IDX 2009. Of 414 companies registered in Indonesian Stock Exchange, 82 companies are randomly taken as sample on the base of proportional allocation using research method with multiple regression and logistic regression. Results of this study show: (1) there is no influence of company size on social statement level of a company in annual report; (2) there is no influence of profitability on social statement level in annual report; (3) there is no influence of leverage on social statement level in annual report; and (4) there is an influence of company operational coverage on social statement level in annual report.  Keywords   :    Social statement, company size, profitability, leverage,  company’s   operational coverage.